Digital Literacy and ICT Self-Efficacy as Determinants of Teachers’ Functional Skills in Islamic Secondary Schools in Pakistan - Chaudhary, Muhammad Kashif Majeed; Tunku Badariah Ahamad; Aizat Bin Shamsuddin (UIN Raden Mas Said Surakarta, 2025)
This study investigates the relationship between digital literacy competence and ICT self-efficacy in shaping functional skills among students in Islamic secondary schools. As digital technologies become increasingly embedded in educational practices, disparities in technological engagement highlight the need to understand how digital competencies influence students’ problem-solving, critical thinking, and descriptive abilities. Employing a quantitative approach, data were collected through structured questionnaires administered to teachers and students in Islamic secondary schools. Statistical analyses, including correlation and moderation tests, were conducted to examine the interrelationships between digital literacy, ICT self-efficacy, and functional skills, as well as to explore potential gender-based differences in technological knowledge and confidence. The findings indicate that higher levels of digital literacy are positively associated with stronger ICT self-efficacy and enhanced functional skills. Gender-based analysis suggests variations in digital confidence and technology use patterns. These results underscore the importance of strengthening digital literacy and self-efficacy to support skill development in faith-based educational settings. The study contributes to educational technology discourse by highlighting the role of digital competence in fostering functional skills and informing more inclusive and effective technology integration strategies in secondary education.